2002
DOI: 10.1097/00007632-200205150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Low-Level Heat Wrap Therapy Provides More Efficacy Than Ibuprofen and Acetaminophen for Acute Low Back Pain

Abstract: Continuous low-level heat wrap therapy was superior to both acetaminophen and ibuprofen for treating low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 26 publications
2
99
0
3
Order By: Relevance
“…Ours findings are consistent with the results of some other studies on the efficacy of thermotherapy and cryotherapy on low back pain relief [12,16,18,19]. In most studies, thermotherapy and cryotherapy were effective, in long term, on pain relief in the patients suffering from low back pain [12,16,20].…”
Section: Discussionsupporting
confidence: 91%
“…Ours findings are consistent with the results of some other studies on the efficacy of thermotherapy and cryotherapy on low back pain relief [12,16,18,19]. In most studies, thermotherapy and cryotherapy were effective, in long term, on pain relief in the patients suffering from low back pain [12,16,20].…”
Section: Discussionsupporting
confidence: 91%
“…Several RCTs were identified on treatments for acute low back pain that were not included in the guidelines: four trials on acupuncture [61][62][63][64], six trials on herbal medicine [65][66][67][68][69][70], one trial on interferential therapy [71], and three References trials on low-level heatwrap therapy [72][73][74]. These interventions were not included in the guidelines, because they were not summarized in a systematic review, involve alternative therapy, or are not commonly used throughout Europe for the treatment of acute low back pain.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…The search retrieved 205 unique articles which resulted in seven trials, reported in six articles [8,9,13,15,17,20] being included in the review (Fig. 1).…”
Section: Identification and Selection Of Trialsmentioning
confidence: 99%
“…Five of the trials reported on participants with acute low back pain [8,13,15,17,20] one trial reported on participants with chronic low back pain [9] and one trial included both participants with acute low back pain and with chronic low back pain as defined for this review [17].…”
Section: Description Of Trialsmentioning
confidence: 99%
See 1 more Smart Citation